Teleophthalmology and use of phelcom eyer technology for screening glaucoma suspects in Campo Grande, MS - Fernandes, Miqueias Oliveira Lima; Pereira, Ana Claudia (Seven Editora, 2024)
Glaucoma is the second leading cause of blindness in the world’s population and the most important cause of irreversible blindness in the world. Individuals not diagnosed with glaucoma may have their quality of life impaired. There is evidence in the literature that the more advanced the glaucoma, the worse the sequelae, which can compromise patients’ daily activities such as reading, driving, walking, judging distances, and seeing objects approaching from the side. DOI:https://doi.org/10.56238/sevened2023.006-149